Physically activated corn cob carbon for congo red and methanil yellow removal - Faridatun Sholehah; Rabiatul Adawiyah; Bahrun Bahrun (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2025)
The conversion of agricultural residues into sustainable adsorbents provides an environmentally responsible pathway for advanced wastewater treatment. In this work, physically activated carbon was synthesized from corncob, an abundant and underutilized agricultural byproduct, through carbon dioxide activation at elevated temperatures. Comprehensive characterization using BET surface area analysis, SEM-EDX, and FTIR confirmed the formation of a highly porous structure with abundant surface functional groups, favourable for dye adsorption. The adsorbent exhibited excellent performance in removing Congo Red (CR) and Metanil Yellow (MY), achieving maximum adsorption capacities of 59.88 mg/g and 30.47 mg/g, respectively. The Langmuir isotherm provides a good description of the equilibrium data, while the kinetic results follow the pseudo-second-order model, indicating that monolayer chemisorption is the dominant mechanism. These findings underscore the potential of corncob-derived activated carbon as a cost-effective, renewable, and high-performance material for sustainable wastewater remediation